Inter-Collaboration Design between ISP CERTs and Security Center for Effective Response of Large-Scale Cyber Attacks - Kim, Kyuil; Cho, Buseung; Lee, Wonhyuk; Kim, Dongkyun; Park, Hyungwoo (International Journal of Engineering and Technology, 2018)
Recently, cyber-threats have been increased every day with most of the information is transmitted by internet. Many institutions perform appropriate countermeasure against cyber crisis. However, they have been considered a partial solution to the problem. The current response for large-scale cyber-attacks is inadequate. Many institutions that provide main service and resource to the user are suffered by cyber-attacks. We propose the effective response method against their cyber threats. Our proposed mechanisms reduce the cyber threats through inter-collaboration design between ISP CERTs and security monitoring and response. While they perform the security monitoring for the only own circuit, the institution use the various networks such as main network and backup network etc. Among their network, ISP CERTs can exist or can’t exist and security center can exist or can’t exist too by the security service policy of ISP. Therefore, while institution reduces the cyber threat through them, the circuit that they don’t exist significantly increases the security threat.  And the institution not only hasn’t the trust for the circuit but also increase in cyber threat because ISP optionally provides the security service. Therefore, we design the inter-collaboration mechanisms of them that rapidly and exactly response the cyber-attacks. We also implement inter-collaboration system based on the global threat management, global network control, RBL(Real-time Blocking List)
Keywords: Cyber-attacks; Inter-Collaboration; ISP CERTs; Security Monitoring & Response; Hacking